ПОБЕДА НА МЕЖДУНАРОДНОМ КОНКУРСЕ - ЛУЧШЕЕ ПРИЗНАНИЕ - Георгиевна Карабекян, Мария (Musical Armenia, 2011)
Musicologist, pedagogue of Stepanakert Sayat-Nova Music College Maria G. Gharabekyan writes the article "The best recognition is the victory in international competition". The author writes that Artsakh Chamber Orchestra "Mrakats", directed by Marine Mesropyan has for first time participated in the international competition "Singing world" in Saint-Pietersburg on 29-3 July 2011 and has won the first prize in the nomination of "Chamber Orchestras" and the second prize in the nomination of "Sacred Music". Except these prizes the orchestra the special prize from the juries.